Exploration Stress and Coping Strategy Among Cardiovascular Patience - Mohamed Sharif Mustaffa; Nurul Aisyah Abdul Hamid (Universitas Negeri Padang, 2019)
The purpose of this study is to explore the cause of stress and coping strategy among cardiovascular patience in Sarawak.  This study is qualitative method whereby the researcher will use semi structured interview.  Five informan was selected to be participating in this study.  The researcher using purposive sampling which mean have characteristics likes heart disease and waiting for the date of operation.  In this study also, the researcher did two times interview session.Result for this cause of stress is informan feel stress because they have to wait for a long period for the operation schedule, family distance, no planning towards retirement and lack of financial.  For coping strategy, majority of the informan used the technique by site seeing around hospital, family support and spending time with peer patients.The finding of this study will be a guideline for the new cardiovascular patience. Furthermore, family members and Pusat Jantung Sarawakwill get new information on how to help cardiovascular patience in the future.